2016
DOI: 10.1080/09168451.2016.1230003
|View full text |Cite
|
Sign up to set email alerts
|

Production of high activity Aspergillus niger BCC4525 β-mannanase in Pichia pastoris and its application for mannooligosaccharides production from biomass hydrolysis

Abstract: A cDNA encoding β-mannanase was cloned from Aspergillus niger BCC4525 and expressed in Pichia pastoris KM71. The secreted enzyme hydrolyzed locust bean gum substrate with very high activity (1625 U/mL) and a relatively high k/K (461 mg s mL). The enzyme is thermophilic and thermostable with an optimal temperature of 70 °C and 40% retention of endo-β-1,4-mannanase activity after preincubation at 70 °C. In addition, the enzyme exhibited broad pH stability with an optimal pH of 5.5. The recombinant enzyme hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…The authors reported that the main products yielded from palm kernel meal were mannose and M2 with smaller amounts of M3, whereas M2 was the major product of copra meal. Besides, it has been suggested that the produced β-mannanase can impressively release the reducing sugars from palm kernel meal-including diet in the gastrointestinal system of broilers and the produced MOSs via this enzyme can be used to enhance animal performance as feed supplements (Harnpicharnchai et al, 2016). In another study, Talaromyces trachyspermus β-mannanase (0.4 g) was incubated with dried coffee waste and locust bean gum (15 mg) in a buffer (pH 4.5) at 50°C for 69 hr in a final reaction volume of 1 ml (Ichinose et al, 2017).…”
Section: D Response Surfacesmentioning
confidence: 99%
“…The authors reported that the main products yielded from palm kernel meal were mannose and M2 with smaller amounts of M3, whereas M2 was the major product of copra meal. Besides, it has been suggested that the produced β-mannanase can impressively release the reducing sugars from palm kernel meal-including diet in the gastrointestinal system of broilers and the produced MOSs via this enzyme can be used to enhance animal performance as feed supplements (Harnpicharnchai et al, 2016). In another study, Talaromyces trachyspermus β-mannanase (0.4 g) was incubated with dried coffee waste and locust bean gum (15 mg) in a buffer (pH 4.5) at 50°C for 69 hr in a final reaction volume of 1 ml (Ichinose et al, 2017).…”
Section: D Response Surfacesmentioning
confidence: 99%
“…2, D273, the acid/base proton donor) (Kumagai et al 2011). Whereas bacterial β-mannanases mainly belong to the GH5 and GH113 families (Fusco et al 2018;Zang et al 2015), the more acid-tolerant and catalytic efficient fungal β-mannanases are grouped into the GH5 and GH26 families (Do et al 2009;Hakamada et al 2014;Harnpicharnchai et al 2016;Katsimpouras et al 2016;Liao et al 2014;Naganagouda et al 2009;Wang et al 2015;Yu et al 2015) (Table 2). More recently, the identification of Man134A, produced by the filamentous fungus Aspergillus nidulans, led to the establishment of the new family of GH134 in the CAZy database (Shimizu et al 2015).…”
Section: β-Mannanasesmentioning
confidence: 99%
“…Similarly, previous studies have reported that dietary supplementation with BS (Neijat et al 2019) and PT (Chung et al 2013) resulted in improved nutritional digestibility in broilers. MAN can effectively release reducing sugar from the diet (Harnpicharnchai et al 2016) and increase the ileal apparent digestibility by reducing the chyme viscosity of broilers (Balasubramanian et al 2018). In addition, the combination of probiotics and exogenous enzymes could increase the apparent digestible energy of the ileum, fat, and starch in the 22-42-d-old broilers and had a greater than additive effect on apparent ileal digestible energy and N-corrected apparent metabolic energy (Wealleans et al 2017).…”
Section: Discussionmentioning
confidence: 99%